2021
DOI: 10.1021/acsomega.1c00062
|View full text |Cite
|
Sign up to set email alerts
|

Designing Organic Electron Transport Materials for Stable and Efficient Performance of Perovskite Solar Cells: A Theoretical Study

Abstract: In this article, electron transporting layer (ETL) materials are designed to enhance the performance and stability of methyl ammonium lead iodide (MAPbI 3 ) perovskite solar cells (PSCs). The optical and electronic properties of the designed ETLs are investigated using density functional theory. The designed ETLs show better charge mobility compared to nickel phthalocyanines (NiPcs). The NiPc, a hole transporting layer material, shows ETL-like behavior for PSCs with the substitution of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…The perovskite material, ABX 3 , is sandwiched between electron transport layers (ETLs) and hole transport layers (HTLs), which are light absorbers. ETLs and HTLs have a pivotal role in charge transportation, separation, and recombination [43]. Examples of HTLs are shown in Figure 1b,c.…”
Section: Methodsmentioning
confidence: 99%
“…The perovskite material, ABX 3 , is sandwiched between electron transport layers (ETLs) and hole transport layers (HTLs), which are light absorbers. ETLs and HTLs have a pivotal role in charge transportation, separation, and recombination [43]. Examples of HTLs are shown in Figure 1b,c.…”
Section: Methodsmentioning
confidence: 99%
“…62 Better solubility is indicated by a high negative value of solvation free energy. 13 Table 4 shows the solubility and chemical hardness(η) of CuPc and X 16 CuPc. F 16 CuPc shows the highest negative value of solubility indicating that it is the most soluble out of all the structures.…”
Section: Solubility and Stabilitymentioning
confidence: 99%
“…[29][30][31] Kumar et al investigated the properties of nickel phthalocyanine (NiPc) and halogen-substituted nickel phthalocyanine (X 16 NiPc, X = I, Br, Cl, F) through DFT and concluded that NiPc and Br 16 NiPc can be used as HTL and ETL, respectively, for a MAPbI 3 -based PSCs. 13 In the present work, we will be studying the properties of CuPc and halogen-substituted copper phthalocyanine (X 16 CuPc, X = I, Br, Cl, F) through DFT and determine their ground state properties, excited state properties and solubility in DMSO. We will establish the usage of copper phthalocyanine as HTLs and fluorinated copper phthalocyanine as ETLs in PSCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that the PCE of PSCs is generally dependent on thickness of the perovskite absorber [12][13][14][15]. Thickness of electron transport layers are also crucial for better efficiencies [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%